Dimensão escatológica da Igreja. Um estudo do capítulo VII da Lumen Gentium - Caliman, Cleto; Oliveira, Renato Alves de (2017)
This Essay aims to present the way the Vatican II Council rediscover Eschatology. A process that was going on since the of the nineteenth century up to the twentieth century as the investigations about the historical Jesus began. This ongoing process reaches the fifties and the sixties of the twentieth Century inspired both by the Hope-Principle of E. Bloch and Moltmann’s Theology of Hope. There is a new understanding of eschatology that moves from Dogmatics’ last treatise to a transcendental dimension that touches the whole of the Christian theology on its very foundations. In this way, we leave behind theology’s classical paradigm based on an essentialist philosophy to a new one reflecting of a philosophy of Human Existence. This change in perspective meets the demands of a new understanding of man in modernity. In our view the Vatican II Council assimilates in its main documents this new perspective as we find for example in the Lumen Gentium cap. VII, where it deals with the eschatological nature of the Pilgrim Church and its union with the Celestial Church.
Nesse trabalho apresentamos como o Concílio Vaticano II entra no processo de redescoberta da escatologia que se deu na virada do séc. XIX para o séc. XX no contexto da investigação sobre o Jesus histórico. Esse processo desemboca nos anos 50 e 60 do séc. XX, sob a inspiração do Princípio-Esperança de E. Bloch, na Teologia da Esperança de J. Moltmann. Passamos da compreensão da escatologia como último tratado da dogmática, os Novíssimos, para uma dimensão transcendental que perpassa toda a teologia cristã desde os seus fundamentos. Desta forma, deixamos para trás o paradigma clássico da teologia que girava em torno da filosofia da essência, para um novo paradigma em torno da filosofia da existência, respondendo às exigências da compreensão do ser humano própria da modernidade. Nossa hipótese é que o Concílio Vaticano II assimila em seus principais documentos essa nova perspectiva e, especificamente, na Lumen Gentium, cap. VII, sobre A índole escatológica da Igreja peregrina e sua união com a Igreja celeste.
Keywords: Vatican II; The History of Salvation; Church; Christology; Eschatology; Vaticano II; História da salvação; Igreja; Cristologia; Escatologia